Relation of Menarche, and Breast and Ovarian Cancer in Women - Bareppady, Sunanda; Nayak, Sabitha (Journal of Health and Allied Sciences NU, 2019)
Cancer is one of the leading causes of death in India and it has become an important public health problem, with more than 800,000 new cases being reported every year. In India, the most frequent cancers usually seen among women are those of cervix, uterus, breast, ovary, lip, oral cavity, and esophagus. Among these, breast and ovarian cancer are seen frequently in Indian women. The study is aimed at finding the relationship of menarche with breast and ovarian cancer, and also determining the association between types of cancer and selected demographic variables. A descriptive study was conducted on a sample consisting of 100 participants at the Justice K.S Hegde Charitable Hospital, Mangaluru. The result showed that majority (56%) of the sample experienced their first menarche at less than 13 years and had no family history of breast or ovarian cancer. Among the 100 women, 62% were diagnosed with breast cancer. There is a significant association between types of cancer and age. The p-value is 0.027 at (p < 0.05) level of significance. The study concluded that there is a significant association between types of cancer with age.
Keywords: menarche; breast cancer; ovarian cancer